Government, Religion and Fake News - Leheza, Yevhen (FISIP UIN Sunan Gunung Djati Bandung, 2023)
Research Problem: This research aims to understand the role of social media in the dissemination of information, especially news, as well as the challenges faced regarding the spread of fake news by individuals who do not verify its accuracy. Research purposes: The aim of this research is to educate social media users to use these platforms wisely, with a focus on understanding the role of social media in the dissemination of information.. Research methods: This research uses a qualitative approach by conducting a literature review and discourse analysis based on Miles and Huberman's theory. Results and Discussion: Although social media plays a vital role in the dissemination of news, it is vulnerable to exploitation by individuals who do not verify its accuracy. Key challenges include a lack of cultural literacy and insensitivity to the information being shared. To tackle the spread of fake news, important steps include implementing robust information filtering, increasing digital literacy, and establishing reporting mechanisms to relevant authorities. Research Implications and Contributions: This research has implications for increasing understanding of the spread of fake news on social media and providing suggestions for addressing this problem. The implications include the need to comply with applicable laws and regulations as well as encouragement for social media users to act responsibly in sharing information online.